2022
DOI: 10.3389/fcell.2022.1055067
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP8 regulates ovarian cancer cell response to cisplatin by suppressing apoptosis

Abstract: The identification of therapeutic approaches to improve response to platinum-based therapies is an urgent need for ovarian carcinoma. Deubiquitinases are a large family of ubiquitin proteases implicated in a variety of cellular functions and may contribute to tumor aggressive features through regulation of processes such as proliferation and cell death. Among the subfamily of ubiquitin-specific peptidases, USP8 appears to be involved in modulation of cancer cell survival by still poorly understood mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…IL-32 is highly expressed by activated T cells (35)(36)(37)(38). DUBs are currently as therapeutic targets in different cancers (23,(39)(40)(41), but they may also influence the cancer microenvironment, including T cells (42). Our data show that the use of proteasome inhibitors and DUB inhibitors affects IL-32 protein levels in T cells, which should be kept in mind when using DUB inhibitors in cancer treatments.…”
Section: Discussionmentioning
confidence: 77%
“…IL-32 is highly expressed by activated T cells (35)(36)(37)(38). DUBs are currently as therapeutic targets in different cancers (23,(39)(40)(41), but they may also influence the cancer microenvironment, including T cells (42). Our data show that the use of proteasome inhibitors and DUB inhibitors affects IL-32 protein levels in T cells, which should be kept in mind when using DUB inhibitors in cancer treatments.…”
Section: Discussionmentioning
confidence: 77%
“…Anti-apoptotic effect of PR-619 was less pronounced. Prior research has shown that inhibition of USP can induce cell death via caspase-dependent apoptosis [ 16 ]. The activation of effector caspases 3/7, which are proteases responsible for protein cleavage, DNA condensation, and other apoptotic markers, is one of the critical steps during the process [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we summarized only DUBs with their known substrates in ovarian cancers. There are more studies on identifying important DUBs such as USP8 and USP19 in ovarian cancers [ 173 , 174 ]. However, in this paper, we could not include them, as their target substrates and underlying mechanism were unknown.…”
Section: Discussionmentioning
confidence: 99%